Model Pembelajaran Problem Based Learnig (PBL) di Kelas Rendah pada Matematika - Sugesti, Nur Idayani (Universitas Sebelas Maret, 2020)
One of the objectives of teaching and learning activities is to improve learning outcomes or student achievement. For this reason, it is very necessary for a teacher to do various ways so that these goals are achieved, including by applying various kinds of learning models that can increase the activeness of students in learning activities in the hope that this will also have an impact on improving student learning outcomes. How to increase the activity of students in low grades is a challenge for teachers because they see their relatively low cognitive development as well as the nature of boredom that is often faced by students in learning activities. An example of a learning model that can be applied to increase the activity of students in low grades in particular is by using the Problem Based Learning (PBL) learning model. With the application of this PBL learning model, students individually and in groups will use various thinking skills to solve problems, especially in learning activities.